Contribution to the knowledge of North-American species Hyperomyzus subgenus Neonasonovia (Aphididae, Aphidinae, Macrosiphini) - Nafría, Juan M. Nieto; Hidalgo, Nicolás Pérez; García-Tejero, Sergio; Ciruelos, Sara I. López; Durante, M. Pilar Mier (Zootaxa, 2017)
American specimens of the Hyperomyzus subgenus Neonasonovia conserved in the collections of the Muséum national d’Histoire naturelle (Paris, France) and the Natural History Museum (London, United Kingdom), have been studied. Data to complement previous descriptions of apterous and alate viviparous females of H. nabali and of apterous viviparae of H. nigricornis, H. inflatus, H. niger and H. pullatus, are presented. Apterous and alate virginogeniae females of H. nigricornis, alate viviparous females of H. inflatus, H. niger and H. pullatus, plus oviparous females of H. nabali, are described for the first time. The morphological and biological variability of H. pullatus is discussed. An identification key for viviparous females of the American species of Neonasonovia is presented for the first time. Microphotographs of apterous and alate viviparous females of H. nabali, H. nigricornis, H. inflatus and H. niger, alate viviparous females of H. pullatus, and oviparous female of H. nabali, are presented.